Inter-machine reliability of the Biodex and Cybex isokinetic dynamometers for knee flexor/extensor isometric, concentric and eccentric tests - de Araujo Ribeiro Alvares, B. J.; Rodrigues, R.; de Azevedo Franke, R.; Cordeiro da Silva, B. G.; Silveira Pinto, R.; Vaz, M. A.; Baroni, B. M. (Physical Therapy in Sport, 2015)
OBJECTIVES: To assess the inter-machine reliability of the Biodex System 3 Pro and Cybex Humac Norm Model 770 dynamometers for knee extensor and knee flexor peak torque measurements in isometric, concentric and eccentric tests. DESIGN: Randomized/crossover. SETTING: Exercise Research Laboratory, Federal University of Rio Grande do Sul (Brazil). PARTICIPANTS: 25 healthy male subjects. MAIN OUTCOME MEASURES: Isometric, concentric and eccentric knee extensor and knee flexor peak torques recorded in the same test procedure performed on both isokinetic dynamometers. One-way ANOVA, intraclass correlation coefficient (ICC), standard error of measurement (SEM) and coefficient of variation (CV) were used to verify significant differences, relative and absolute reliability between devices. RESULTS: No significant differences were found between tests performed on Biodex and Cybex (p > 0.05). ICC values indicated a high to very high reproducibility for isometric, concentric and eccentric peak torques (0.88-0.92), and moderate to high reliability for agonist-antagonist strength ratios (0.62-0.73). Peak torque did not show great difference between dynamometers for SEM (3.72-11.27 Nm) and CV (5.27-7.77%). Strength ratios presented CV values of 8.57-10.72%. CONCLUSION Maximal knee extensor and knee flexor tests performed in isometric (60° of knee flexion), concentric and eccentric modes at 60°/s in Biodex and Cybex dynamometers present similar values.